2012
DOI: 10.1007/s11434-011-4933-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the radiation balance of different urban underlying surfaces

Abstract: An urban net all-wave radiation parameterization scheme is evaluated using annual datasets for 2010 recorded at a Beijing urban observation site. The statistical relationship between observed data and simulation data of net radiation has a correlation coefficient of 0.98 and model efficiency of 0.93. Therefore, it can be used to simulate the radiation balance of Beijing. This study analyzes the variation in the radiation balance for different underlying surfaces. To simulate radiation balance differences, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
(27 reference statements)
0
15
0
1
Order By: Relevance
“…Secondly, the ocean might have a moderating effect to temperature anomalies of coastal cities. Thirdly, some biophysical parameters, such as the albedo of the surface material types in urban areas, may be higher than in surrounding areas [2]. In addition, other climate factors like more clouds and precipitation also had an impact on the phenomenon.…”
Section: The Distribution Pattern Of the Suhiimentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the ocean might have a moderating effect to temperature anomalies of coastal cities. Thirdly, some biophysical parameters, such as the albedo of the surface material types in urban areas, may be higher than in surrounding areas [2]. In addition, other climate factors like more clouds and precipitation also had an impact on the phenomenon.…”
Section: The Distribution Pattern Of the Suhiimentioning
confidence: 99%
“…Although cities cover a tiny fraction of the world's surface, urban areas are the nexus of human activity, with more than 50% of the global population and 7%-90% of economic activity [1]. Urbanization changes climatic systems, threatens biodiversity, and affects ecosystem productivity through disturbing energy balance and habitats and the loss of carbon storage and biomass [2,3]. In fact, against the backdrop of climate change, cities have been regarded as ideal natural laboratories for global change studies, particularly valuable in elucidating future climate and environmental change as cities experience elevated temperatures decades ahead of the projected average global warming [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cui et al (2012) showed that annual average net radiations for four land use types of forest, grass, roads and buildings ranged of 38.2-53.4 W/m 2 , and minimum on the grass surface and maximum on the road surface. The urbanization that transferred from forest or grass to road or from grass to building will lead to increasing net radiation.…”
Section: The Climatic Impacts Of Urbanizationmentioning
confidence: 99%
“…The spatial heterogeneity of urban landscapes leads to a non-uniform transmission and distribution of energy radiation. Because the urban area is a complex physical interface, the thermodynamic and kinetic properties of the underlying surface may be substantially changed by modifying the physical characteristics of that surface (Wang and Gong, 2010;Cui et al, 2012). These factors result in cities that have unique climatic characteristics.…”
Section: Introductionmentioning
confidence: 99%